Technology Transfer and Spillovers in International Joint Ventures - Thomas Müller; Monika Schnitzer (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
This paper analyzes the effects of a potential spillover on technology transfer of a multinational enterprise and on the host country policy. In particular, we examine how both parties' incentives can be controlled through the ownership structure in an international joint venture. In contrast to existing arguments we show that spillovers must not always have negative effects on technology transfer and they may be efficiency improving. Moreover, there are circumstances where a joint venture is mutually beneficial. Surprisingly, however, we find that despite the prospect of spillovers a joint venture is sometimes not in the interest of a host country.
urn:nbn:de:bvb:19-epub-93-7
Keywords: D43; F21; F23; L13; P31; O12; 330; Foreign Direct Investment; Joint Venutres; Ownership Structure; Multinational Enterprise; Spillovers; Transition Economics